Os contratos de transporte no novo código civil: conceito, abrangência e conflito de leis - Silveira, Gabriel Tosetti (2011)
A simple reflection about the term "transport" indicates an activity millennially known and widespread, given that their development is mixed and incorporated in the evolution of humanity as a whole. As could be expected, analysis of transportation contracts conducts its legal complexity and its characteristics, analyzed here by a brief review of legislation, beginning with the omission of the Civil Code of 1916 regarding the matter, culminating with the Coding regarded by the law of 2002. With the advent of New Civil Code it´s been a sensible alteration in the interpretation´s rules of contract law, essentially in the order to ensure, through the principles and general provisions, the balance in private affairs rather than the absolute freedom of negotiation. Through principle foundations, legal, doctrinal and jurisprudential sought to repaginate the concept and scope of contracts of transports, from the terms convey, transmit and translate, setting a limit to the performance of the new rules provisions of the Civil Code. Special attention was given to the wording of Articles 731 and 732 of the New Civil Code, which seek a coordinated implementation of various acts that orbit the transport contracts, for example, special laws, among them the Code of Consumer Protection, treaties and conventions ratified by Brazil, as well as norms from authorization, concession and permission of the government. Doctrine and jurisprudence were the tools used in an attempt to harmonize all these standards, with the basic principle the need for constant dialogue between the sources, which should prevail so that the law is applied in its fullness